EXPECTATIONS OF PROSPECTIVE ENTREPRENEURS FROM INSTITUTIONS - DR. J. MARY SUGANTHI BAI (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Micro Small Medium Enterprises generate production at low capital, utilizing indigenous raw materials and local skills, maintaining balanced regional growth and preventing the migration of labour from rural area to urban area. They provide an improved allocation of resources for the best interest of their enterprises as well as the country. They are the pioneers initiating structural changes in the economy. They strive to increase productivity and quality of output through the application of more efficient production techniques, better plant layout and effective marketing policies; they ensure production of better quality goods and services at the lowest cost. The study of entrepreneurship has relevance today, not only because it helps entrepreneurs better to fulfill their personal needs but because of the economic contribution of the new ventures to the country. This current study inspects the expectations of prospective entrepreneurs from financial and non-financial institutions.